E-201 Intravascular ultrasound evaluation of a transverse sigmoid junction meningioma causing dural venous sinus stenosis. (23rd July 2022) - Heiferman, D; Arthur, A; Nickele, C
Abstract : Introduction/Purpose: Dural venous sinus stenosis (DVSS) has been recognized as an etiology of pulsatile tinnitus. Stenosis causes laminar blood flow disruption with transmittance of the turbulence to the inner ear. In addition to routine evaluations of the dural venous sinuses including angiography and physiologic evaluation of through manometry, the use of intravascular imaging modalities, including intravascular ultrasound (IVUS), has been described. We present the first case of the use of IVUS to evaluate a meningioma causing DVSS. Materials/Methods: A 49 year old woman with migraine headaches and left sided, low frequency, pulse-synchronous tinnitus was found to have a 12mm meningioma overlying the left transverse sigmoid junction with associated DVSS. The meningioma remained stable for two years, however the pulsatile tinnitus became more severe to the point of affecting the patient's quality of life. In addition to routine endovascular evaluation, the off-label use of IVUS was discussed with the patient to further characterize the meningioma in relation to the sinus, including the presence of sinus invasion versus external compression A catheter angiogram demonstrated tumor blush of the meningioma fed by the left middle meningeal artery and a 45% diameter stenosis of the left transverse sigmoid junction. There was no evidence of alternative arterial or venous causes of pulsatile tinnitus. Through a 0.056 inch inner-diameter catheter in the left jugular bulb, a 160cm length 0.027 inch inner-diameter microcatheter with a J'ed 300cm 0.014 inch microwire were navigated through the left transverse sinus, across the torcular and into the right jugular vein. No significant pressure gradient was found across the stenosis and there was no change in waveform morphology. A microcatheter exchange was performed for the IVUS microcatheter (Eagle Eye Platinum, Volcano, San Diego), which is a monorail system. Two separate manual pull back IVUS recordings were performed from the mid-left transverse to mid-left sigmoid sinuses. Results: A hyperechoic concavity of one wall of the sinus at the left transverse sigmoid junction was well visualized, consistent with the meningioma. A 67% cross sectional stenosis was measured without evidence of sinus invasion by the tumor, inferred by a smooth sinus wall. ( Figure 1 ) Conclusion: This case demonstrates the feasibility of intravascular imaging to characterize the relationship between a meningioma and dural venous sinus. Higher resolution imaging modalities, including intravascular optical coherence tomography or angioscopy may further elucidate this relationship. Future studies are needed to correlate intravascular imaging with intraoperative findings. Disclosures: D. Heiferman: None. A. Arthur: None. C. Nickele: None.